PEDAGOGICAL CULTURE OF THE FUTURE TEACHER, ITS ROLE IN TEACHING AND EDUCATION OF THE CHILD’S PERSONALITY IN THE INTEGRATED ENVIRONMENT - Mykytyuk, I.A. (Pedagogy of Higher and Secondary Education, 2009)
The article is devoted to the research of the importance of pedagogical culture of a future teacher. The pedagogical condition of future teacher’s pedagogical culture (integrity , continuity, rystematic character) formation have been dearmined in the article.